Kemampuan Menulis Karangan Deskripsi Menggunakan Powerpoint Pada Siswa Kelas V Sekolah Dasar - Dea Aldina Lestari; Indah Nurmahanani; Acep Ruswan (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research is motivated by the low ability to write descriptive essays shown by many students who have difficulty in finding and pouring ideas or ideas into writing, writing is less precise including the use of Indonesian language, spelling capital letters, dot punctuation, comma punctuation and others. This study aims to find out: 1) improve the ability to write description essays using powerpoint; 2) find out the factors that affect the ability to write description essays; 3) find out the solution to overcome the ability to write description essays using powerpoint. The type of research used is qualitative description research. The sample of this study was fifth grade students in one of the elementary schools in Subang Regency totaling 15 students. based on the results of the study, the conclusions were obtained: 1) the test results of the ability to write descriptive essays using powerpoint fall into the sufficient category; 2) Factors that affect the ability to write descriptive essays are internal factors and external factors 3) Solutions or efforts that can be made to overcome these obstacles can be done by teachers and parents, starting from providing encouragement or motivation to students and appreciating every little thing that is done, communicating good things. Keywords : Writing Skill ; Description essay ; Powerpoint